Molecular characterization of three Vibrio species and study its pathogenic potential in a gnotobiotic Artemia model - Z. Z., Nurfarizatul; N. K. P., Diyana; F. M., Amirah; Mohd Yaminudin, Nur Jasmin; Karim, M.; Md Yasin, Ina Salwany (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
Vibriosis remains the main problem in aquaculture industry caused by bacteria from the genus Vibrio. This study was developed to identify and differentiate between the three Vibrio species which are Vibrio harveyi, V. alginolyticus and V. parahaemolyticus by PCR-outer membrane protein (ompW) gene. Three specific bands with size of 643 bp were produced and sequence analysis of three Vibrios used in this study showed high similarities of V. harveyi, V. alginolyticus and V. parahaemolyticus with published sequences, respectively. Thus, ompW gene can be used as phylomarker in differentiating Vibrio isolates. The effect of pathogenicity of local Vibrios strains with different concentrations on host-microbe interaction has been studied in the gnotobitic Artemia. After challenged, investigation revealed that maximum mortality of Artemia was observed at the concentration of 107 CFU/mL with V. parahaemolyticus have a highest mortality rate.